Development of sulfonated carbon-based catalysts derived from palm kernel shell for acetylation of glycerol - Usman Idris, Nda-Umar (2020)
The production and utilization of biodiesel have led to a significant increase in its by-product, glycerol, leading to a glut and value depreciation. Catalytic conversion of glycerol to acetin, a versatile industrial chemical, is one of the routes to improve its utilization. Currently, the homogeneous catalysts deployed are associated with many negative effects, while some of the existing heterogeneous catalysts exhibits low selectivity to triacetin, which is the most valued product. Carbon-based material, palm kernel shell (PKS), was processed and carbonized using direct, chemical, and template methods under CO2 environment and subsequently functionalized using inorganic, organic, and hybrid of organic-inorganic sulfonating agents. The catalysts were characterized using proximate analysis, acid-base titration, CHNS analyzer, X-ray diffraction (XRD), Fourier transform infra-red (FTIR) spectroscopy, temperature programmed desorption of ammonia (TPD-NH3), N2 physiosorption analysis (BET), scanning electron microscopy coupled with energy dispersive X-ray spectroscopy (SEM-EDX), thermogravimetric-differential thermogravimetric analysis (TGA-DTG), Raman spectroscopy, X-ray photoelectron spectroscopy (XPS) and solid state Nuclear Magnetic Resonance (NMR) spectroscopy, respectively. The carbon-based catalysts were deployed in glycerol acetylation and the product was analyzed using gas chromatography coupled with mass spectrometer (GC-MS), gas chromatograph equipped with flame ionization detector (GC-FID), FTIR and NMR. The catalyst obtained via template carbonization method at 800℃ exhibited excellent glycerol conversion (GC) with the highest triacetin selectivity. On optimization using RSM based on two-level, three-factor, face-centred central composite design (23 CCD), 97% GC and selectivity of 4.9, 27.8, and 66.5% monoacetin (MA), diacetin (DA), and triacetin (TA) were achieved under the optimum conditions of temperature 126±2℃, glycerol-to-acetic acid mole ratio (G/AA) 1:10.4, and catalyst load (CL) 0.45 g in 3 h reaction time. Amongst the organosulfonic acid functionalized catalysts, the ethanesulfonic acid (ESA) catalyst exhibited the highest TA selectivity and on optimization using RSM, 99.03% GC and selectivity of 6.91, 54.86, and 37.71% MA, DA, and TA were achieved at the optimum conditions of temperature 120±2℃, G/AA mole ratio 1:8, CL of 0.69 g and 3 h reaction time. Furthermore, the carbon-based catalyst obtained from the functionalization using the hybrid mixture of concentrated ethanesulfonic acid and sulfuric acid (1:9) exhibited excellent results after optimization. 99.8% GC and selectivity of 1.48, 24.64, and 73.81% MA, DA, and TA, respectively, were obtained under optimum conditions of temperature 110±2℃, G/AA mole ratio 1:10, and catalyst load 0.6 g in 3 h reaction time. On validation, all the model results exhibited good fit with good agreement between the predicted and the experimental data with the determination coefficient (R2) > 0.9500 and adequate signal-to-noise ratio >4. The high performance of the synthesized carbon catalysts was attributed to the synergistic effect of good physicochemical characteristics, including good textural properties and high acidic site density and very importantly, the configuration of the surface acid moieties on the catalyst allowing unhindered access to the active sites during the reaction. On evaluating the reusability and stability of the selected catalysts in five reaction cycles each, they maintained excellent performance in glycerol conversion but inferior in TA selectivity after the first use. The DA selectivity became higher in the subsequent reaction cycles. The instability of TA was due to the leaching of active sites (-SO3H).